O problema da fundamentação de uma história universal no sistema crítico-transcendental de Kant - Klein, Joel Thiago (2008)
This thesis deals with the problem of the foundations of a Universal History on the bases of the Kantian critical-transcendental system. Its objective is to demonstrate that the theme of Universal History possesses transcendental legitimacy, that is to say it can be seen from the horizon of the Copernican Revolution of thinking. In the first chapter, the nature of the project of a Universal History is characterized and it is sustained that the reflections about history form a unitary and coherent doctrine. In the second chapter, the transcendental legitimacy of the notion of teleology is reconstructed from the Critique of Judgement and it is shown how teleology determined the conception of history. In the last chapter, it is defended that Universal History should be seen as a response to the question what may I hope? and, consequently, as founded on a particular human interest of reason.